2021
DOI: 10.1007/s00426-020-01473-3
|View full text |Cite
|
Sign up to set email alerts
|

Detecting faking-good response style in personality questionnaires with four choice alternatives

Abstract: Deliberate attempts to portray oneself in an unrealistic manner are commonly encountered in the administration of personality questionnaires. The main aim of the present study was to explore whether mouse tracking temporal indicators and machine learning models could improve the detection of subjects implementing a faking-good response style when answering personality inventories with four choice alternatives, with and without time pressure. A total of 120 volunteers were randomly assigned to one of four exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…This is consistent with the standard doctrine in cognitive psychology that increased cognitive processing causes delays in response times [8,9] including in speech [10,11]. Even deception without speech, such as in responding dishonestly on personality questionnaires, yields longer response times than responding honestly [12][13][14]. Arousal accounts of deception highlight that lying may cause greater anxiety [15], which increases muscle tension throughout the body including the muscles of the larynx that control the voice [16,17], resulting in higher vocal pitch [18,19].…”
Section: Introductionsupporting
confidence: 82%
“…This is consistent with the standard doctrine in cognitive psychology that increased cognitive processing causes delays in response times [8,9] including in speech [10,11]. Even deception without speech, such as in responding dishonestly on personality questionnaires, yields longer response times than responding honestly [12][13][14]. Arousal accounts of deception highlight that lying may cause greater anxiety [15], which increases muscle tension throughout the body including the muscles of the larynx that control the voice [16,17], resulting in higher vocal pitch [18,19].…”
Section: Introductionsupporting
confidence: 82%
“…The results suggested that mental rotation abilities and the resilience of attention together with some pathological personality indicators (i.e., Psychoticism, Disconstraint; Negative Emotionality; Introversion) are useful measures in identifying drivers caught for violations and probably differentially subjected to impression management or self-deception. Despite the results presented here, and the importance of personality in affecting driving behaviors, self-reported personality measures should be considered with caution [ 108 ] considering their exposure to faking good, especially in forensic assessments in which they could potentially lead to paradoxical effects. Furthermore, these results may be a relevant source of knowledge for researchers dealing with both the prediction of motor vehicle-crashes and the driver’s liability in such events [ 109 ], providing information about variables that are able in detecting drinker drivers.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we would like to encourage researchers to contrast indirect questioning techniques such as the CWM with alternative approaches to measuring and controlling the influence of deliberate faking on self-reports such as, for example, social desirability scales [3,80,81], behavioral indicators [82][83][84], lie detection and the bogus pipeline [85][86][87], and the overclaiming technique [88][89][90]. Such extended studies could help identify those methods-or possibly even a combination of methods-that optimally counteract the detrimental influence of deliberate positive self-presentation on the validity of self-reports.…”
Section: Plos Onementioning
confidence: 99%